Short Supply of High Levels of Guanidine Acetic Acid, Alters Ovarian Artery Flow and Improves Intraovarian Blood Perfusion Area Associated with Follicular Growth in Sheep - Marta da Costa Sousa; Camila Muniz Cavalcanti; Alfredo José Herrera Conde; Bruna Vitória de Freitas Alves; Larissa Fernandes Baia Cesar; Jhennyfe Nobre de Sena; Yohana Huicho Miguel; César Carneiro Linhares Fernandes; Juliana Paula Martins Alves; Dárcio Ítalo Alves Teixeira; Davide Rondina (Animals)
Guanidinoacetic acid (GAA), a precursor of creatine, has a recognized effect on ruminant performance when used as a dietary supplement. However, its impact on reproductive response remains to be elucidated. Therefore, this study aimed to contribute initially to this area by supplementing the diets of ewes with a high dose of GAA, evaluating its effects on reproductive response. Twenty adult sheep had their estrus synchronized using an MPA sponge, eCG, and PGF2α. After estrus detection ewes were mated. For 10 days until mating, ewes were grouped in groups of baseline diet (BSD; n = 10) and GAA diet (GAAD; n = 10), which was the BSD with daily 0.9 g/kg DM of GAA. After the eCG + PGF2α dose, the GAAD group exhibited an increase in the peak diastolic and pulsatility of the ovarian artery, a reduction in the systolic/diastolic peaks ratio, and a larger intraovarian blood perfusion area. A greater depletion of follicles with <3 mm was observed in the GAAD group and a higher number of follicles ≥3 mm. No differences were observed between the diets respect to pregnancy, and twin rates. Thus, a high GAA supply before mating significantly alters ovarian vasculature and improves follicular growth in ewes but does not affect the pregnancy rate.